Tratamento de ambiguidades em requisitos de evolução de sistemas jurídicos baseado em mapeamento conceitual - Aguiar, Luiz Gustavo Ferreira (2017)
Software Engineering is a participatory process that involves all stakeholders actively in design. On a complex domain, such as juridical area, users and domain experts have an important role in requirements elicitation process, especially in composition of evolution requirements for existing systems, whereas that requirements specification must specific to domain. However, ambiguities are everyday event in juridical area, reason associated own nature of domain and predominant use of natural language. Such ambiguities are reflected in the evolution requirements of juridical software systems, users and domain experts, causing problems of understanding for systems analysts. The conceptual maps are introduce as cognitive tool, being appropriate for use in communication processes. This work applies conceptual maps in the level of communication between users and juridical experts to system analysts, with the goal to reduce ambiguities in evolution requirements of juridical systems. A model was designed and tested by experimentation, with application of a functional prototype to undergraduate students and law professionals. The results points the ambiguities reduction of unclarity category, showing that proposed methodology provides better interpretation of the software evolution requirements of the juridical domain systems for systems analysts and easy making user requirements.